Network analysis of psychological resilience, personality traits, and depression–anxiety–stress symptoms among military college students in China - Hou, Yanqin; Zhang, Guimin; Mi, Mingdi; Wang, Buyao; Feng, Tingwei (Frontiers in Psychiatry, 2026)
BackgroundNon-military-status undergraduate cadets in Chinese military academies face a distinctive combination of academic demands and militarized stressors, which may increase psychological distress and shape resilience-related adaptation. Although personality traits are associated with psychological resilience, systematic evidence is still lacking regarding how resilience and personality jointly relate to depression–anxiety–stress symptoms in quasi-military contexts.MethodsThis cross-sectional study examined the associations among psychological resilience, Big Five personality traits, and depression–anxiety–stress symptoms in 855 non-military-status undergraduate cadets. Participants completed the 10-item Connor–Davidson Resilience Scale (CD-RISC-10), the Chinese Big Five Personality Inventory (CBF-PI-15), and the Depression Anxiety Stress Scales–21 (DASS-21). Network estimation was performed using graphical LASSO with Spearman partial correlations. Centrality indices, including bridge strength and bridge expected influence (BEI), were computed to identify key nodes and their roles in the overall network structure.ResultsThe gender-stratified CD-RISC-10–CBF-PI–DASS-21 networks were relatively dense, with 19/36 and 25/36 non-zero edges and similar mean edge weights. Network comparison tests indicated significant differences in overall structure (M = 0.12, p <.001) and global strength (3.89 vs. 4.04; S = 1.15, p = .01), suggesting tighter coupling among resilience, personality, and distress indicators in females. In both networks, resilience exhibited the most prominent bridging role, whereas agreeableness functioned as a shared protective bridge node. The strongest positive bridge edge differed by gender. Bridge metrics showed good stability, and bootstrap confidence intervals supported the accuracy of edge-weight estimates.ConclusionThis study provides clinically informative, network-based evidence on psychological adaptation in a rarely examined cadet population. The central bridging role of resilience, the protective bridging role of agreeableness, and gender-specific trait–resilience linkages offer actionable, empirically grounded targets for stratified psychological interventions and resilience-promotion programs in high-demand, quasi-military training settings. These findings have important implications for psychological support strategies and mental health promotion in military education environments.